Amplification of competitive telomere sequence in living animal cells induces chromatin instability - Mizuarai, Shinji (Kluwer Academic Publishers, 1999)
We have reported the establishment of new episomal-type expression vector the copy number of which can be readily regulated by a temperature shift. In this study, we attempt to apply this vector for the functional analysis of the noncoding regions of DNA. A plasmid containing a 0.45 kb-telomere repeat sequence was constructed and transfected into simian CV-1 cells, leading to successful establishment of cell lines in which episomal telomere sequence could be amplified by temperature shift. When the episomal telomere sequence was amplified, the cells stopped proliferating at the G(2)/M phase of the cell cycle and exhibited a large size with flattened morphology and several small nucleus-like particles. These cells expressed Cdk inhibitor p21 and β-galactosidase, which are expressed in some senescent cells. Microscopic analysis revealed frequent end-to-end attachments of chromosomes, which resulted in a variety of aberrant chromosome configurations. None of these characteristics was observed in nontransfected and control plasmid-transfected CV-1 cells at any cultivation temperature. These results indicate the usefulness of our vector system in analyzing telomeric DNA.